Report of the workshop on data and knowledge in deep-sea fisheries in the high seas : (Food and Agriculture Organization of the United Nations, 2008)
This document contains the report of the Workshop on Data and Knowledge in Deep-sea Fisheries in the High Seas held in Rome from 5 to 7 November 2007. The Workshop was convened to review an initial draft of the International Guidelines as called for by the FAO Committee on Fisheries at its twenty-seventh session in 2007. This expert consultation was preceded by the Expert Consultation on Deep-sea Fisheries in the High Seas, held in Bangkok, in November 2006. The consultation adopted a draft of the international guidelines to be forwarded on to a technical consultation for review and adoption.